Supplementation in mushroom crops and its impact on yield and quality - Carrasco, Jaime; Zied, Diego C. [UNESP]; Pardo, Jose E.; Preston, Gail M.; Pardo-Giménez, Arturo (Springer Nature, 2018)
Mushroom supplementation is an agronomic process which consists of the application of nutritional amendments to the substrates employed for mushroom cultivation. Different nitrogen and carbohydrate rich supplements have been evaluated in crops with a substantial impact on mushroom yield and quality; however, there is still controversy regarding the nutritional requirements of mushrooms and the necessity for the development of new commercial additives. The addition of external nutrients increases the productivity of some low-yielding mushroom varieties, and therefore is a useful tool for the industry to introduce new commercially viable varieties. Spent mushroom compost is a waste material that could feasibly be recycled as a substrate to support a new commercially viable crop cycle when amended with supplements. On the other hand, a new line of research based on the use of mushroom growth promoting microorganisms is rising above the horizon to supplement the native microbiota, which appears to cover nutritional deficiencies. Several supplements employed for the cultivated mushrooms and their agronomic potential in terms of yield and quality are reviewed in this paper as a useful guide to evaluate the nutritional requirements of the crop and to design new formulas for commercial supplementation.
Keywords: Agronomy; Mushroom cultivation; Nutrition; Quality; Substrate; Yield